The Chemical and Nutritional Properties of Processed Fruit Enriched with Algae - Somayeh Ranjbar-Shamsi; Anousheh Sharifan; Mozhgan Emtyazjoo; Maryam Moslehishad (Journal of Food Quality)
Currently, processed fruits (sour fruit and fruit paste) are consumed as one of the most popular goodies in the some countries, and the position of this product in the food basket of Iranian families is gradually becoming important. Algae are an excellent potential source of natural compounds that can be used as a functional food. The aim of this study was to investigate the effect of Sargassum ilicifolium, Ulva lactuca, and Gracilaria cortica algae at different concentrations (1.5 and 3%) on the chemical and nutritional properties of processed fruit formulations. Fatty acid profiles were measured by gas chromatography. Vitamin contents were measured using HPLC. Inductively coupled plasma (ICP) was used to measure minerals. In the fatty acid profile, 21 fatty acids including saturated fatty acids, unsaturated fatty acids, and PUFAs were identified. The predominant fatty acids in samples were palmitic acid, stearic acid, oleic acid, and linoleic acid. E and B1 vitamins varied from 6.19 to 22.63 mg/g and 5.38–19.10 mg/g in sour fruits and fruit paste, respectively. Among the minerals, iodine was at the highest level in all samples (5.06–607.46 mg/g). In conclusion, these seaweeds can be used as a suitable source of fatty acids, minerals, and vitamins in the formulation of functional processed fruits, which are essential for human health.